A new contribution to the knowledge of Neotropical Eumeninae (Hymenoptera, Vespidae) - Ferreira, Wellington D.; Grandinete, Yuri C.; Lopes, Rogério B.; Hermes, Marcel G. (Zootaxa, 2015)
A new species, Pirhosigma sulcata Ferreira & Hermes, sp. nov. is described from the Brazilian Amazon; the male of Pararhaphidoglossa gibbiventris Giordani Soika, 1978 is described for the first time. Pseudodynerus carpenteri Hermes & Melo, 2008 is newly recorded from Brazil. New collecting data are reported for Pseudodynerus griseus (Fox, 1902) and P. subapicalis (Fox, 1902).